Implications of the Private Property Right to the Community Forest Businesses Formalization through the Certification Policy - Bramasto Nugroho; Tatang Tiryana (Jurnal Manajemen Hutan Tropika, 2013)
This study aimed to analyze the implication of formalization of community forest business efforts through mandatory timber legality certification policy. Field survey was conducted in March–April 2012 in 3 districts in Central of Java namely Blora, Wonogiri, and Wonosobo District. The results showed that community forest is mainly planting in their private owned land. It brings 2 consequences. Firstly, their willingness to manage their forest sustainably was emerged without any enforcement from external parties. Secondly, there were autonomous in decision making in their way to manage their forest such as they only planted tree species that easy to sell and valuable, they only cut their trees when they need huge money for children schooling, marriage, illness, and housing. The autonomous decision making gives also the owners (farmers) other alternatives to utilize their land otherwise planting the trees. It is mean, if the policy is decreasing the potential benefits from growing the trees, they can also convert their community forest into other business in which profitable and easy to sell their products. From those facts, it seems the formalization of community forest business through mandatory certification is not a proper policy to enhance the community forest.